Evolution of on-resistance (RON) and threshold voltage (VTH) in GaN HEMTs during switch-mode operation. (May 2018) - Chini, Alessandro; Iucolano, Ferdinando
Abstract: The evaluation and investigation of electrical parameters drifts during device operation is one of the mandatory task that has to be performed in order to improve GaN-power devices stability. In this work the authors would like to present a novel characterization method that allows the simultaneous monitoring of both RON and VTH during the switch-mode operation. By applying the proposed measurement method with different operating parameters it has been possible to provide a preliminary interpretation of the physical mechanisms leading to the observed RON increase and VTH positive shift. In particular, the observed RON increase, which is thermally activated with a 0.83 eV activation energy, has been ascribed to the presence of Carbon-related traps within the device buffer layer. On the other hand, the positive VTH shift has instead been related to interface defects at the dielectric/III–N interface and/or to bulk traps in the gate dielectric.